PSV-27 Program Chair Poster Pick: Expression QTL mapping for meat quality in beef cattle. (30th November 2020) - Mateescu, Raluca G; Leal-Gutiérrez, Joel; Elzo, Mauricio
Abstract: Expression QTL mapping provides information about genetic variant with modulatory effects on gene expression which are useful for understanding the genetic architecture of complex phenotypes. This mapping allows for uncovering of genomic regions associated with transcription regulation of genes which can be related to phenotypic variation when they colocalize with QTLs (cis and trans effects), providing a molecular basis for the phenotype-genotype association. The objectives of the present research were to perform eQTL mapping for meat quality traits in longissimus dorsi muscle and to uncover genes whose expression is influenced by local or distant genetic variation. A total of 120 steers from the University of Florida Beef Unit multibreed Angus-Brahman herd born between 2013 and 2014 were used in this study. The first three principal components from a principal component analysis for all meat quality phenotypes were used to construct a meat quality index. Eighty animals were selected based on extreme meat quality index for mRNA sequencing and 100 bp paired-end reads were mapped against to the Btau_4.6.1 reference genome. eQTL mapping was performed using 112, 042 SNPs and 8, 588 genes. A cis QTL was defined as an SNP located no more than 1 Mb upstream of the transcription start site or downstream of the transcription end site of an annotated gene. Polymorphisms associated with expression of at least 20 genes in the case of eQTL were considered hot spots. The harboring or adjacent gene was defined as master regulators. Multiple cis eQTLs and sQTLs effects were identified and genes such as LSM2, SOAT1, TTN and TEK are a few examples of potential expression and splicing regulatory genes. A total of 27 expression and 13 splicing master regulator genes were uncovered, mainly cytoskeletal or membrane-associated proteins, transcription factors and DNA methylases.